2013
DOI: 10.1038/cmi.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Full screening and accurate subtyping of HLA-A*02 alleles through group-specific amplification and mono-allelic sequencing

Abstract: HLA-A*02 is the most prevalent and polymorphic major histocompatibility complex (MHC) allele family in humans. Functional differences have been revealed among subtypes, demanding further subtyping of HLA-A*02 in basic and clinical settings. However, the fast growing polymorphisms render traditional primer- or probe-based typing methods impractical and result in increasing ambiguities in direct sequence-based typing. In this study, we combined group-specific amplification and mono-allelic sequencing to design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…Normal tissue DNA isolated from FFPE CRC blocks was genotyped for HLA-A*02:01 status by Sanger sequencing using specific oligonucleotide primers for the amplification of a region spanning the 5′ end of exon 2 of the HLA-A locus with an upstream intronic region. This region encompasses a single-nucleotide variant that allows to distinguish HLA-A*02 from non-HLA-A*02 genes 40 and thus high accuracy classification of samples as HLA-A*02:01 positive or HLA*02:01 negative 72 . For amplification, the following oligonucleotide primers were designed according to a protocol published in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal tissue DNA isolated from FFPE CRC blocks was genotyped for HLA-A*02:01 status by Sanger sequencing using specific oligonucleotide primers for the amplification of a region spanning the 5′ end of exon 2 of the HLA-A locus with an upstream intronic region. This region encompasses a single-nucleotide variant that allows to distinguish HLA-A*02 from non-HLA-A*02 genes 40 and thus high accuracy classification of samples as HLA-A*02:01 positive or HLA*02:01 negative 72 . For amplification, the following oligonucleotide primers were designed according to a protocol published in ref.…”
Section: Methodsmentioning
confidence: 99%
“…In order to specifically address HLA-type dependence of immunoediting, HLA-A*02:01 status was determined in MSI CRC and EC 40,41 . HLA-A*02:01 was present in 34 (47.9%) of 71 MSI CRC and 13 (47.1%) of 27 MSI EC samples, in line with proportions reported for German populations (prevalence of HLA-A*02:01: 46.2%, n = 39,689, www.allelefrequencies.net).…”
Section: And Supplementary Data 2)mentioning
confidence: 99%
“…ANN method precisely determined three promising T cell epitopes within MP88; 166 YMAADQFCL174,158VSYEEWMNY 166and 236 FQQRYTGTF 244 .These epitopes could potentially induce CD8+ T cell immune response when interacting strongly with MCH I alleles such as YMAADQFCL/HLA-A*02:01 ,FQQRYTGTF/ HLA-B*15:01 and VSYEEWMNY/ HLA-A*29:02. These promising epitopes interact with the most predominant HLA class II allele in human like HLA-A*02:01 [49,50], in same time will provide protection against Cryptococcal infection for 93% of world population in case if used in forward vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…72,73 Another study showed that the VEE platform with mutated-fused E6 and E7 proteins was able to generate 100% protection from tumor challenge in vaccinated mice and eliminate 90% of established tumors in HLA-A Ã 0201 transgenic mice, 74 which is important given that HLA-A Ã 02 is the most prevalent MHC I allele family in humans. 75 As for both bacterial and viral based HPV vaccines, immune recognition of components inhibits repeat vaccination with the same delivery system, therefore a heterologous prime-boost strategy may be best for these platforms to maximize the immune response to target HPV antigens.…”
Section: Protein and Peptide Vaccinesmentioning
confidence: 99%